The sixth giant? Environmental policy and the Labour government, 1945–51 - Fitzpatrick, Tony (Cambridge University Press, 2016)
The connections between social and environmental policies have a longer and more fertile history than is often appreciated. Ignoring that history is not just unfortunate in its own terms but may mean that we deprive ourselves of resources that could be useful in the future. Unfortunately, social policy histories avoid discussion of the natural environment, just as environmental histories avoid discussion of welfare services. This article therefore seeks to open up new debates and a new field of research. It focuses upon one of the key periods in the development of UK state welfare, the Labour government of 1945–51. It argues that Labour displayed an ambivalence toward the natural environment. Land nationalisation had long been an aspiration, but Labour drew back from its more radical ambitions. In policy terms, this gave rise to a dualism. Town and country planning became one of its enduring legacies, but more socialistic, redistributive measures fell by the wayside.